Communication in the Engineering Curriculum: Learning to Write and Writing to Learn - Dahm, Kevin D.; Farrell, Stephanie; Ramachandran, Ravi P. (Journal of Engineering Education Transformations, 2015)
Good communication skills are vital for practicing engineers, and there is much literature on strategies for developing communication skills in engineering students. For some years there has been a growing trend in engineering education towards treating communication as an inter-disciplinary skill, and seeking meaningful and pedagogically sound ways to integrate communication skills throughout the engineering curriculum. This paper presents a summary of literature related to writing in the engineering curriculum. It is intended to provide practical resources for engineering faculty, presenting both general guiding principles for writing in the curriculum and specific models that have been used successfully in engineering courses and are readily adaptable in a variety of engineering courses and curricula. The two primary considerations examined are (1) strategies for introducing disciplinary writing into engineering courses and (2) strategies for engaging students in reflective writing.